The Implementation of Moral Education With Methodology of Remembrance, Thought and Compassion at Dar al Hikmah Islamic Boarding School Mlarak Ponorogo - Moh Mukhlas; Nurul Siam Fajriani (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Darul Hikmah Islamic Boarding School Blebakan Nglumpang Mlarak Ponorogo is one of the educational institutions that is oriented towards the application of moral education, especially for children with backgrounds in Orphans, Orphans and Disabilities to become a generation with morality and the spirit of the Qur'an. Through the Fikir approach, Pondok Pesantren Zikir and Wisdom Darul Kasih Darul not only teaches knowledge, but more than that also teaches the life of Rahmatan Lil'alamin to have the Soul of the Qur'an. From this background, the research objectives are: 1) Describe the Implementation of Moral Education through the approach of Dhikr, Thinking and Compassion in the Darul Hikmah Islamic Boarding School. 2) Explain the Supporting and Inhibiting Factors of the Implementation of Moral Education through the approach of Dhikr, Thinking and Compassion in the Darul Hikmah Islamic Boarding School. This research is a qualitative research with a case study approach. To get the data needed, researchers used three methods, namely the Interview Method, Observation Method, Documentation Method. To analyze the data, researchers used the Interactive analysis of the Miles and Huberman model with the steps for Data Reduction, Data Presentation, and Image Conclusion. Analysis of the data found is the implementation of moral education through the approach of thinking, dzikr and affection in the Wisdom of Darul Hikmah Islamic Boarding School using the thought approach, remembrance approach, compassion approach. Supporting and inhibiting factors Implementation of moral education through the approach of thinking, dhikr and compassion ie teachers who master subject matter in their respective fields, teachers are alumni of Islamic boarding schools, many teachers live in Islamic boarding schools to guide children, availability of comfortable places to children's learning.